Effect of excess PbO on microstructure and mechanical properties of (Pb0.975Ba0.025)ZrO3ceramics - T. Bongkarn (2018)
(Pb0.975Ba0.025)ZrO3(PBZ2.5) ceramics were fabricated from their oxide mixture via the solid state reaction method. Excess PbO (1, 3, 5 and 10 wt%) was added together with starting materials to compensate for PbO loss from evaporation during calcination and sintering. The phase structure was analyzed by XRD. Pure PBZ2.5 phase was observed in all of the PBZ2.5 samples. Density, dielectric and mechanical properties were measured. The experimental results suggest that 1 wt% excess PbO is the optimal level to obtain the best properties of the ceramics. The results were discussed in terms of the mechanisms of densification. © 2005 Elsevier B.V. All rights reserved.